2012
DOI: 10.1016/j.toxlet.2012.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular toxicity of cis-2-pentenenitrile in the rat

Abstract: A c c e p t e d M a n u s c r i p t >Oral cis-2-pentenenitrile causes loss of vestibular function in rats >Loss of hair cells in the vestibular sensory epithelia causes the functional deficit >CYP blocker 1-aminobenzotriazole blocks the vestibular effect of cis-2-pentenenitrile >Oral cis-2-pentenenitrile does not cause significant neuronal degeneration system apart from neurite labeling in the olfactory glomeruli. We conclude that cis-2-pentenenitrile causes vestibular toxicity in a similar way to allylnitril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Therefore, this model may be useful to identify the cellular and molecular basis of vestibular dysfunction and recovery associated with chronic ototoxicity and washout. Although the literature contains a noticeable number of references on the CNS toxicity of IDPN ( Wang et al, 2015 ), their value is dubious as they ignore the firmly established fact that the effects of IDPN on spontaneous motor behavior are a syndrome of vestibular dysfunction ( Llorens et al, 1993 ; Llorens and Rodríguez-Farré, 1997 ; Boadas-Vaello et al, 2005 ; Soler-Martín et al, 2007 ; Saldaña-Ruíz et al, 2012a , b ). The test battery used in the present study to assess vestibular dysfunction is highly specific and not affected by the alleged CNS effects of IDPN ( Llorens and Rodríguez-Farré, 1997 ; Seoane et al, 1999 ; Boadas-Vaello et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this model may be useful to identify the cellular and molecular basis of vestibular dysfunction and recovery associated with chronic ototoxicity and washout. Although the literature contains a noticeable number of references on the CNS toxicity of IDPN ( Wang et al, 2015 ), their value is dubious as they ignore the firmly established fact that the effects of IDPN on spontaneous motor behavior are a syndrome of vestibular dysfunction ( Llorens et al, 1993 ; Llorens and Rodríguez-Farré, 1997 ; Boadas-Vaello et al, 2005 ; Soler-Martín et al, 2007 ; Saldaña-Ruíz et al, 2012a , b ). The test battery used in the present study to assess vestibular dysfunction is highly specific and not affected by the alleged CNS effects of IDPN ( Llorens and Rodríguez-Farré, 1997 ; Seoane et al, 1999 ; Boadas-Vaello et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…One cause of vestibular dysfunction is inner ear damage following exposure to ototoxic chemicals. These include therapeutic drugs, such as aminoglycoside antibiotics and the chemotherapeutic agent cisplatin, as well as a number of workplace chemicals and environmental pollutants ( Forge and Schacht, 2000 ; Sergi et al, 2003 ; Hodgkinson and Prasher, 2006 ; Schacht et al, 2012 ; Saldaña-Ruíz et al, 2012a , b ; Sedó-Cabezón et al, 2014 ). A well-established result of ototoxic insult is the loss of the sensory hair cells (HCs) responsible for mechanotransduction in both the vestibular and auditory systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While cis-crotononitrile caused behavioral effects and vestibular hair cell loss (1-3, 2-4, and 3-5 vestibular ratings as compared with control ( 0-1 ratings ) in both rats 11 ) ( 80, 100, and 120 mg / kg / day, for 3 days ) and mice 20) , trans-crotononitrile (250 mg/kg/day, for 3 days) caused rearing deficits with no vestibular dysfunction or hair cell loss 11) , but caused the same behavioral syndrome and hair cell loss in mice 20) . Rats receiving 1.5, 1.75, and 2.0 mmol / kg of cis-2-pentenenitrile displayed reduced rearing activity in the open field and increased rating scores on the vestibular dysfunction test battery as well as hair cell loss (1-3, 1-4, and 3-4 vestibular ratings as compared with control (0-1) 12) . Dose-response studies on allyl showed the match between behavioral effects and hair cell loss in mice 21) .…”
Section: Toxicitymentioning
confidence: 93%
“…A significant correlation has been shown between acute toxicity and the octanol/water partition coefficient for nitriles, including allyl nitrile 7) . Rodents administered allyl nitrile at high doses exhibited behavioral abnormalities 8) ; this is not known to occur with other mononitriles, with the exception of crotononitrile and 2-pentenenitrile [9][10][11][12] . The dinitrile 18) Fos induction in the brain of mice after allyl nitrile administration…”
Section: Toxicitymentioning
confidence: 99%